PENGARUH UPAH, PENDIDIKAN, DAN PERTUMBUHAN EKONOMI TERHADAP KESEMPATAN KERJA SERTA KEMISKINAN PROVINSI JABAR BAGIAN SELATAN - iksan, muhamad; Arka, Sudarsana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 1 (2022): VOL 11 NO 1, JANUARI 2022 [1-403 ], 2022)
This study aims to analyze the effect of wages, eduThis study aims to analyze the effect of wages, education, and economic growth on employment opportunities in the southern part of West Java Province, analyze the influence of wages, education, economic growth, and employment opportunities on poverty in the southern part of West Java Province, and find out the indirect effects of wages, education, and economic growth towards poverty through employment opportunities in the southern part of West Java Province. The data used in this research is data panel for ten years, namely in 2008-2017 from five regencies in the southern part of West Java Province. The data analysis technique used in this study is path analysis. Based on the results of the analysis show that wages and economic growth do not affect employment opportunities while education has a positive and significant effect on employment opportunities. Wages and employment opportunities have a negative and significant effect on poverty, while education and economic growth have no effect on poverty. Job opportunities do not mediate the influence of wages and economic growth on poverty, but employment opportunities mediate the effect of education on employment. cation, and economic growth on employment opportunities in the southern part of West Java Province, analyze the influence of wages, education, economic growth, and employment opportunities on poverty in the southern part of West Java Province, and find out the indirect effects of wages, education, and economic growth towards poverty through employment opportunities in the southern part of West Java Province. The data used in this research is data panel for ten years, namely in 2008-2017 from five regencies in the southern part of West Java Province. The data analysis technique used in this study is path analysis. Based on the results of the analysis show that wages and economic growth do not affect employment opportunities while education has a positive and significant effect on employment opportunities. Wages and employment opportunities have a negative and significant effect on poverty, while education and economic growth have no effect on poverty. Job opportunities do not mediate the influence of wages and economic growth on poverty, but employment opportunities mediate the effect of education on employment.